Handbook of obstetric high dependency care - Vaughan, David, MBBS (Wiley-Blackwell, 2010)
"High dependency facilities are now an essential component of modern obstetric practice. The acutely ill parturient is now cared for by a multidisciplinary team within this specialised area. A patient does not present with a diagnosis but with an array of signs and symptoms which the staff caring for her must be able to detect, investigate and act upon. This handbook aims to assist obstetricians, midwives, nurses and anaesthetists involved with the maternity high dependency unit in three ways: to provide an understanding of why these units are now a necessity to enhance safe obstetric care; to help obstetric units develop their own high dependency unit; and most importantly to assist with the treatment of clinical problems that occur in the ill parturient. It is not intended to be an exhaustive tome on the minutiae of obstetric pathology and medicine. However, we hope it will act as a practical bedside guide to help to achieve our goal of safer maternal care"--Provided by publisher